2013
DOI: 10.1007/s10815-013-0129-4
|View full text |Cite
|
Sign up to set email alerts
|

Quality of embryos transferred and progesterone levels are the most important predictors of live birth after fresh embryo transfer: a retrospective cohort study

Abstract: Purpose To identify the independent predictors of live birth following IVF, and to assess the role of cohort-specific parameters, including antral follicle count (AFC), the number of oocytes retrieved, the total number of embryos, and the total number of good-quality embryos, in fresh IVF cycles. Methods A retrospective cohort study of 2,525 infertile women undergoing IVF between 2002 and 2007. The hypothesis that the number and quality of embryos transferred capture the effects previously attributed to cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
2
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 37 publications
1
17
2
3
Order By: Relevance
“…There is some evidence to suggest that elevated progesterone also results in a decreased formation of highquality embryos [9]. Progesterone has been found to be an independent predictor of pregnancy in IVF cycles, with higher P4 levels being associated with a decreased likelihood of pregnancy [10]. While higher progesterone was noted in patients with lower blastulation rates in our study, this did not reach statistical significance.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…There is some evidence to suggest that elevated progesterone also results in a decreased formation of highquality embryos [9]. Progesterone has been found to be an independent predictor of pregnancy in IVF cycles, with higher P4 levels being associated with a decreased likelihood of pregnancy [10]. While higher progesterone was noted in patients with lower blastulation rates in our study, this did not reach statistical significance.…”
Section: Discussioncontrasting
confidence: 81%
“…These patients with high blastulation rates are not necessarily the patients with the most oocytes retrieved, which may surprise some patients who believe that high oocyte yield is associated with universally better outcomes. Improved blastulation rate and formation of [10]. In a large retrospective cohort study, higher blastulation rate was associated with a higher incidence of tubal and uterine factor infertility, whereas low blastulation rates were associated with a higher rate of unexplained infertility [11].…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, parallel research has also shown that high serum P4 at trigger has a positive or direct correlation on the number of oocytes retrieved, without an obvious effect on quality [3, 6, Fig. 2 Receiver operator characteristic curve for live birth and ongoing pregnancy rate when compared to any negative %ΔP4 with AUC 0.692 [15][16][17]. A study of the cumulative effects of fresh and FET cycles has shown that elevated serum P4, previously repeatedly reported to have a negative impact on LBR, may actually depend on ovarian response [15].…”
Section: Discussionmentioning
confidence: 99%
“…Простая аналитика, учитывающая коли-чество проведенных исследований со времени пер-вого отчета [1], и к слову сказать их уже более 60, с противоречивыми, а порой противоположными вы-водами, прямое тому свидетельство.Влияние повышенного уровня прогестерона на эффективность ЭКО В то время как некоторые исследователи сооб-щили о снижении клинической эффективности ЭКО у пациенток с высокой концентрацией проге-стерона в день введения хорионического гонадотро-пина человека (чХГ) [2][3][4][5][6][7][8][9][10] Повышение сывороточной концентрации прогестерона в конце фазы стимуляции оказывает негативное влияние на клинические показатели успешности ЭКо. Между тем, имея сразу ряд однозначных исследований и даже метаанализов, с практической точки зрения справедливым все же будет утверждение, что пока нет никаких убедительных доказательств того, что абсолютное количественное значение уровня прогестерона может расцениваться как безоговорочное указание на целесообразность продолжения протокола ВрТ или, напротив, как указание на его прекращение на эмбриологическом этапе.…”
unclassified
“…В своем исследовании Q. Cai и соавт. [5] пришли к выводу, что число эм-брионов хорошего качества и уровень прогестерона на день введения чХГ являются двумя важнейшими независимыми предикторами живорождения после свежего цикла ЭКО. При этом перспективы бере-менности начали снижаться после превышения уровня прогестерона 0,6 нг/мл.…”
unclassified